P215 In a treatment-naïve, early rheumatoid arthritis cohort, baseline ultrasound power Doppler synovitis and tenosynovitis are highly associated with remission when treated with first line etanercept + methotrexate (MTX) but not MTX alone. (23rd April 2022) - Shukla, Rudresh; Hum, Ryan; Ho, Pauline; Wakefield, Richard J; Emery, Paul; Buch, Maya H
Abstract: Background/Aims: Clinical remission is the treatment target in rheumatoid arthritis (RA). In a treatment-naïve, early RA trial (VEDERA: 'Very early Etanercept and Methotrexate versus Methotrexate with/without Delayed Etanercept in RA'), we previously reported the presence of ultrasound power Doppler synovitis (PDUS) at diagnosis that improved in the majority with treatment. For this study, we aimed to investigate specifically for an association of baseline PDUS and PD tenosynovitis (PDTS) with subsequent clinical remission (DAS28ESR ≤ 2.6) in VEDERA, also comparing the two treatment groups. Methods: The 'VEDERA' trial randomised 120 treatment-naïve, new-onset RA patients to either first-line etanercept+methotrexate (ETN+MTX) or methotrexate treat-to-target (MTX-TT) regime with escalation to ETN+MTX if not in DAS28ESR remission at week 24. Clinically symptomatic and dominant hand (MCP 1-5, wrist, flexor tendons 1-5 and extensor carpii ulnaris tendon) ultrasound assessments were completed at baseline, weeks 12, 24 and 48. PDUS and PDTS were assessed semi-quantitatively and converted to dichotomous (absent = total score 0, present = total score ≥ 1) for this logistic regression analysis. Results: At baseline, 68% (81/120) demonstrated PDUS and 68% also demonstrated PDTS overall. In the MTX-TT group, 63% (38/60) had PDUS and 62% (37/60) had PDTS at baseline. In ETN+MTX group, 72% (43/60) had PDUS and 75% (45/60) had PDTS at baseline. As per randomised trial, there were no differences in baseline demographics, DAS28ESR and HAQ between the groups. Overall, baseline PDUS was associated with week 24 remission and baseline PDTS was associated with week 24 and 48 remission (table 1 ). Baseline PDUS was particularly associated with week 24 remission in the ETN+MTX group, with a high OR (95% CI) of 6.83(1.2 - 38.91) compared to the MTX-TT group [1.75(0.5 - 6.14)]. Baseline PDTS was also associated with a high OR for week 48 remission in the ETN+MTX group (OR [95% CI] 9.13[1.77 - 47.02]) in contrast to an absence of association in the MTX-TT group. Conclusion: Baseline PDUS and PDTS are associated with remission in early RA patients treated with TNF-inhibitor treatment. These measures may be useful to stratify patients early for TNF bDMARD to attain the target of clinical remission in RA. Disclosure: R. Shukla: None. R. Hum: Other; R.H holds an Academic Clinical Fellowship funded by the National Institute for Health Research (NIHR) through the Integrated Academic Training (IAT) Programme. P. Ho: None. R.J. Wakefield: None. P. Emery: None. M.H. Buch: None.